Bedding Plane Effects on Mechanical Behavior of Surrounding Rock in Mountain Tunneling - Shuang You; Jincui Sun; Hongtao Wang (Shock and Vibration)
The layered rock showed the characteristics in Mountain tunnel, Yunnan. A series of uniaxial compression tests and variable angle shear tests were carried out, and the aim was to investigate the effect of the bedding on its mechanical parameters and failure modes. The test results show that the uniaxial compressive strength, elastic modulus, and Poisson's ratio of layered rock present a U-shaped distribution with the increase in bedding orientation from 0° to 90°. All of them have a maximum when the bedding orientation is 0° and a minimum when the bedding orientation is 45°. The failure modes of layered rock can be summarized into three types: the fracture tensile failure parallel to the weak plane of bedding; the shear slip failure along bedding weak plane; and tension-shear composite failure between bedding weak plane and matrix. Based on the testing data and analysis results, it can be concluded that the layered rock specimen with different bedding orientations is an important reason for the anisotropy of mechanical parameters and failure modes.